2017
DOI: 10.1152/ajpendo.00203.2016
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline directly modulates muscle protein synthesis via the PI3K/MAPK/4E-BP1 pathway in a malnourished state: evidence from in vivo, ex vivo, and in vitro studies

Abstract: (CIT) is an endogenous amino acid produced by the intestine. Recent literature has consistently shown CIT to be an activator of muscle protein synthesis (MPS). However, the underlying mechanism is still unknown. Our working hypothesis was that CIT might regulate muscle homeostasis directly through the mTORC1/PI3K/MAPK pathways. Because CIT undergoes both interorgan and intraorgan trafficking and metabolism, we combined three approaches: in vivo, ex vivo, and in vitro. Using a model of malnourished aged rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
3
25
0
2
Order By: Relevance
“…However, the mechanism by which CIT provides the necessary energy for this process is not fully understood. Interestingly, most of the studies showing a positive effect of CIT on muscle protein synthesis observed this under conditions of protein/energy deficiency . We observed a similar pattern here, with CIT‐stimulated protein synthesis exclusively detected after amino acid/serum deprivation or mild uncoupling, when ATP/ADP ratios were decreased, but not in standard conditions ( Figure ).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, the mechanism by which CIT provides the necessary energy for this process is not fully understood. Interestingly, most of the studies showing a positive effect of CIT on muscle protein synthesis observed this under conditions of protein/energy deficiency . We observed a similar pattern here, with CIT‐stimulated protein synthesis exclusively detected after amino acid/serum deprivation or mild uncoupling, when ATP/ADP ratios were decreased, but not in standard conditions ( Figure ).…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, most of the studies showing a positive effect of CIT on muscle protein synthesis observed this under conditions of protein/energy deficiency. 1,3,31 We observed a similar pattern here, with CIT-stimulated protein synthesis exclusively detected after amino acid/serum deprivation or mild uncoupling, when ATP/ADP ratios were decreased, but not in standard conditions (Figure 1). CIT stimulated protein synthesis while ATP/ADP ratios, respiration, and AMPK activation remained unchanged.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations